10 years observation study of low and moderate cardiovascular risk hypertensive patients: the impact of anxiety and depression level in development of cardiovascular complications. (25th November 2020) - Smirnova, M.D; Blankova, Z.N; Barinova, I.V; Fofanova, T.V; Svirida, O.N; Ageev, F.T
Abstract: : Not only "classic" risk factors such as age, sex, smoking status, blood pressure (BP) and cholesterol (HS) levels, but also additional factors, one of which is the psychological status of the patient, need to be considered to improve the prediction of cardiovascular complications. This is especially true for low/moderate risk patients on the SCORE scale, whose risk of cardiovascular complications (CVC) is often underestimated. Aim: To assess the contribution of psychological status of hypertensive patients and SCORE<5% to increase the risk of development of cardiovascular complications for a period of 10 years of observation. Materials and methods: In 2009, 142 hypertensive patients with SCORE risk <5% (37 men and 105 women) in addition to the clinical examination, were interviewed on the HADS scale to assess the level of anxiety and depression. In 2019, these patients were interviewed by phone for CVC suffered over the past 10 years: all-cause mortality, cardiovascular death (CVD), fatal and nonfatal myocardial infarction (MI), stroke, revascularization, hospitalization for cardiac events. Results: At the time of inclusion in the study, the age of the patients was 50, 9±8.2 years. At the first visit systolic BP (SBP) level was 130.0 (128.4; 133.7) mm Hg and diastolic BP (DBP) 80.0 (81.3; 84.5) mm Hg. The HS level was 6.1 (5.9; 6.3) mmol/L, triglycirides 1.4 (1.5:1.8) mmol/L, low dencity lipoproteins 3.8 (3.6; 4.0) mmol/L, high density lipoproteins 1.3 (1.4; 1.5) mmol/L. Level of anxiety (A) was 7.0 (7.0; 8.2) points, depression (D) – 5.7 (5.2; 6.2) points. The patients without the expressed symptom of D (0–7 points) – 76.8% (n=109), A (0–7 points) – 52% (n=74). The patients with clinically significant D (>11 points) – 8.5% (n=12), A (>11 points) – 18.3% (n=26). 2 CVD occurred in the observed group in 10 years (1.4%), 6 MI, 12 percutaneous coronary intervention (8 acute coronary syndrome), 4 strokes, 34 cardiovascular hospitalizations. 14 new onset cases of coronary artery disease (9.6%). Thus 31.7% of observed patients had CVC. Comparison of the initial data of the group with CVC with the group without CVC revealed a difference only in the level of D: 7.0 (5.6; 7.3) points in patients with CVC vs 5.0 (4.7; 5.8) p=0.04) – Fig. 1. The patients were comparable in sex and age. BP, lipid profile, glucose, heart rate, smoking status, levels of A did not differ significantly. Multi-factor regression analysis has demonstrated that depression levels D is an independent predictor of the development of complications in a model involving age, sex, BP, HS and A (β=0, 218, p=0, 03). Conclusion: Level D is an independent risk factor development of CVC in hypertensive patients low/moderate risk on SCORE. Funding Acknowledgement: Type of funding source: None